Bencana dan Tindakan Kepedulian Sosial dalam Keberagamaan: Studi Komparasi Kitab Suci al-Qur’an dan Alkitab - Abdul Qadri (UIN Sunan Gunung Djati Bandung, 2021)
Indonesia is a country with a high potential for disaster threat, from BNPB (National Disaster Management Agency) data until September 3, 2020, nearly 4 million people died and 637 religious facilities were damaged. However, the enthusiasm of caring for its people, including disaster victims, Indonesia is included in the top 10 categories of the most generous countries in the world. On the other hand, the disaster in the two holy books of the majority of religions; Islam and Christianity tell a lot about the catastrophic events of the past people that were befallen those who disobeyed God. However, all the disastrous events that occurred were also experienced by those who obey God. For this reason, this article focuses on disasters as a phenomenon in the perspective of the Koran and the Bible, as well as how both of them respond to continuous and recent disaster events that seek to find a foundation and a common ground for both in responding to disaster phenomena in religious reality. This study uses a descriptive-comparative analysis method of the Qur'an and the Bible. This paper finds that (1) al-Qur'an and the Bible at least agree with the concept of disaster as God's will which is also related to human activity. (2) The response to disasters in the two books is similar in several ways, it's just that in the Bible disaster is sometimes interpreted as a sign of God's